Outcome benefits to transurethral resection of the prostate in patients with benign prostatic hyperplasia at Medan regional hospital - Richman Patandung; Syah Mirsya Warli (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Benign prostatic hyperplasia (BPH) is a pathologic process that cause of lower urinary tract symptoms (LUTS) in aging men. Transurethral resection of the prostate (TURP) is still the current gold standard of BPH treatment. International Prostate Symptoms Score (IPSS) and the quality of life (QoL) index are used for assessing the TURP results.Objective: This study would like to show the benefits outcome of TURP in patients with BPH evaluated with IPSS score and QoL index in Medan regional hospital.Methods: This research is a retrospective study of BPH patients that is treated with TURP at Universitas Sumatera Utara Hospital from September 2019 – August 2020. Patients will be divided into 2 groups, group 1 with patients who have a prostate size <80 grams and the second group with a prostate size> 80 grams. All patients who were included in this study were assessed for their complaints using the IPSS and QoL index before and after taking an operation. Statistical analysis was performed using independent t test and Mann Whitney test. The data were significant if the p value < 0.05. Results: There are 60 patients enrolled in this study that treated with TURP. The mean age of patients in the group 1 was 69.57 ± 7.698 years and 69.84 ± 5.893 years in the group 2. There is no significant difference between group 1 and group 2 in postoperative IPSS and QoL results (p >0.05). Conclusion: TURP procedure is preferable option of BPH for patients in any prostate size.